Just Making It Up: Structure and Spontaneity in Music and Teaching: An interview with W.A. Mathieu by Noam Lemish - Lemish, Noam (Critical Studies in Improvisation / Études critiques en improvisation, 2022)
William Allaudin Mathieu (born in 1937) is a consummate musician, a pianist, composer, author, and teacher — and, in my view, one of the most influential musicians of his generation. In his early twenties he composed music for the Kenton and Ellington Big Bands, was the founding musical director of the famed Second City of Chicago (Improv Theater) and was a pioneer in the 1960s of the application of theater improvisation games into the musical sphere. He is the author of four influential books, including the best selling "The Listening Book" (1991). In a teaching career spanning more than fifty years, Mathieu has been an important influence and guide to many musicians worldwide. As I demonstrate throughout this essay, W.A. Mathieu reminds us that in highlighting the world of improvisation we must be careful not to romanticize spontaneity, for doing so might well involve our falling into the trap of dualistic thinking that separates if not excludes such activity from composition. Overall, Mathieu implores us to reflect deeply about false dichotomies as improvisation/composition, and by extension think more broadly about the perils of dualistic thinking in general. In exploring themes in discussion of improvisation, I highlight some of the ways in which we can begin to draw connections between Mathieu’s ideas and the usefulness of improvisation to pedagogy in music education and beyond.